MODERN SURGICAL TREATMENT METHODS OF CHOLEDOCOLITHIASIS - Yusupova , Shaxnozaxon (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The issues of treatment of choledocholithiasis (stone disease in the bile duct) using modern surgical minimally invasive methods are discussed. Choledocholithiasis is one of the most dangerous and severe forms of biliary system diseases, and if not detected in time, it causes severe complications such as mechanical jaundice, choledochitis, and pancreatitis. The article studies the clinical and functional effectiveness of endoscopic retrograde choledocholithotomy (ERC) and laparoscopic choledocholithotomy. According to the results of the study, minimally invasive technologies cause less trauma to the patient's body than traditional open surgical procedures, reduce the frequency of postoperative complications, and significantly shorten the rehabilitation period. These results scientifically substantiate the advantages of modern endoscopic and laparoscopic approaches in the treatment of choledocholithiasis and indicate the need for their widespread application in practice.